Navigating Deixis in Political Discourse: An Examination of Zelensky and Putin’s Speeches - Siti Nur Aenul Hasanah; Devian Try Gustary; Bayu Andika Prasatyo (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The purpose of this research and analysis is to understand the types of deixis and the meaning of deixis contained in Zelensky and Putin's speeches. In analyzing and conducting research on the types and meanings of deixis in speech texts, the writer uses a pragmatic approach. The author applies Yule's (1996) theory of deixis. In completing this analysis, the author uses a qualitative description as an analytical method. The research data is in the form of sentences containing deixis elements in the text of Zelensky and Putin's speeches as data sources and grouped into types of deixis. The results of this study indicate that the types of deixis include people deixis, place deixis, and time deixis used in Zelensky and Putin's speech texts. The use of person deixis has meaning to the participant or actor. The use of place deixis means place or location. The use of time deixis has meaning at the time of the incident. About the research Here is a comparison between the speeches of Zelensky and Putin. In Zelensky's speech, the dominating deixis is place deixis. This is because in his speech Zelensky always uses the word “this” which means place, namely the country of Ukraine. And in Putin's speech the dominating Deixis is people's deixis. This is because in Putin's speeches he always repeats the word "We" which means Russian citizen